Isolation and propagation of human corneal stromal keratocytes for tissue engineering and cell therapy - Nur Zahirah Binte M. Yusoff (2023)
The human corneal stroma contains corneal stromal keratocytes (CSKs) that synthesize and deposit collagens and keratan sulfate proteoglycans into the stromal matrix to maintain the corneal structural integrity and transparency. In adult corneas, CSKs are quiescent and arrested in the G0 phase of the cell cycle. Following injury, some CSKs undergo apoptosis, whereas the surviving cells are activated to become stromal fibroblasts (SFs) and myofibroblasts (MyoFBs), as a natural mechanism of wound healing. The SFs and MyoFBs secrete abnormal extracellular matrix proteins, leading to corneal fibrosis and scar formation (corneal opacification). The issue is compounded by the fact that CSK transformation into SFs or MyoFBs is irreversible in vivo, which leads to chronic opacification. In this scenario, corneal transplantation is the only recourse. The application of cell therapy by replenishing CSKs, propagated in vitro, in the injured corneas has been demonstrated to be efficacious in resolving early-onset corneal opacification. However, expanding CSKs is challenging and has been the limiting factor for the application in corneal tissue engineering and cell therapy. The supplementation of serum in the culture medium promotes cell division but inevitably converts the CSKs into SFs. Similar to the in vivo conditions, the transformation is irreversible, even when the SF culture is switched to a serum-free medium. In the current article, we present a detailed protocol on the isolation and propagation of bona fide human CSKs and the morphological and genotypic differences from SFs.